A comparative study of supraglottic airway devices blockbuster LMA versus BASKA mask in adult patients undergoing laparoscopic cholecystectomy under general anesthesia - Shubam Achari,; Chavi Sethi,; Roopesh Kumar, (Asian Journal of Medical Sciences, 2025)
Background: Supraglottic airway devices (SADs) have been extensively utilized as an alternative to tracheal intubation in the context of general anesthesia. Aims and Objectives: The study aimed to compare the utility of the new supraglottic airway Blockbuster and Baska Mask (BM) in patients undergoing laparoscopic cholecystectomy under general anesthesia. Materials and Methods: This prospective, single-blind, randomized study included 160 participants who underwent laparoscopic cholecystectomy at our tertiary care institute from May 2023 to May 2024. Participants were randomly assigned to two groups: Group I received the BM, whereas Group II received the Blockbuster laryngeal mask airway (LMA). The groups were compared in terms of demographic characteristics, ease of insertion, number of attempts, insertion time, oropharyngeal sealing pressure (OSP), adequacy of ventilation, hemodynamic changes, and complications. Independent samples t-test was used to compare continuous variables, whereas the chi-square test was used to assess associations between categorical variables. Results: The demographic characteristics of the two groups were comparable, with no significant differences (P>0.05). Our findings indicated that the number of attempts, ease of insertion, insertion time, and hemodynamic variables did not differ significantly between the two groups (P>0.05). Conclusion: Both SADs, the Blockbuster LMA and the BM, can be safely employed during general anesthesia and positive pressure ventilation for laparoscopic cholecystectomy. The Blockbuster LMA demonstrated a shorter insertion time compared to the BM, along with superior OSP.